Obecne spojrzenie na rehabilitację Zespołu Odpychania (Zespołu Pushera). Przegląd literatury oraz doświadczenia własne = The current look of repulsion on pusher syndrome. Review of the literature and our own experience - Tomaszewska, Edyta; Cichosz, Michał; Kochański, Bartosz; Plaskiewicz, Anna; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Tomaszewska Edyta, Cichosz Michał, Kochański Bartosz, Plaskiewicz Anna, Zukow Walery. Obecne spojrzenie na rehabilitację Zespołu Odpychania (Zespołu Pushera). Przegląd literatury oraz doświadczenia własne = The current look of repulsion on pusher syndrome. Review of the literature and our own experience. Journal of Education, Health and Sport. 2015;5(2):196-207. ISSN 2391-8306. DOI: 10.5281/zenodo.16042 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A196-207 https://pbn.nauka.gov.pl/works/545775 http://dx.doi.org/10.5281/zenodo.16042 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. Obecne spojrzenie na rehabilitację Zespołu Odpychania (Zespołu Pushera). Przegląd literatury oraz doświadczenia własne The current look of repulsion on pusher syndrome. Review of the literature and our own experience Edyta Tomaszewska1, Michał Cichosz1,2, Bartosz Kochański3, Anna Plaskiewicz3, Walery Zukow4 1Jolly Med Szpital rehabilitacyjny Popielówek. Oddział rehabilitacji neurologicznej 2Fundacja Wsparcie Kowary 3Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu, Polska 4Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska Streszczenie Zespół odpychania jest klasycznie definiowany jako zaburzenie postrzegania orientacji ciała w płaszczyźnie czołowej. Główną przyczynę zespołu odpychania stanowią uszkodzenia mózgu, zarówno o podłożu udarowym jak i nie spowdowane przez sam udar. Pacjenta z zespołem odpychania charakteryzuje wychylenie w stronę porażoną i opór na zewnętrze próby przywrócenia do pionu. Na podstawie piśmiennictwa oraz badań własnych autorzy przedstawili główne przyczyny, objawy i metody leczenia zespołu odpychania. Summary Pusher syndrome is classically described as a disorder of body orientation in the frontal plane. The main cause of the Pusher syndrome is brain demage and due either to stroke or to other factors. Pusher behaviour is characterized by a tilt towards the contralesional paretic side and resistance to external attempts to rectify it. Authors describes on the basis of the literature and his own research, the symptoms and methods of treatment of pusher syndrome. Słowa kluczowe: zespół Pushera, neurorehabilitacja. Key words: Pusher syndrome, neurorehabilitation.